The Phenomena of Spreading of Hydrotalcite Sol on A Porous Silica Surface Governed by Marangoni Effect - Helwani, Z.; Aziz, N.; Shamsudin, I. K.; Othman, M. R. (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Wetting phenomena plays a crucial role in a wide range of technological applications. Spreading of liquids on solids involving phase change is encountered in many areas ranging from biological systems to industrial applications such as coatings, printing, painting and spraying. The fundamental study on wetting of membrane precursors namely hydrotalcite sols on a porous silica surface with different types of precursor material was successfully carried out. Relationship between the contact angle of a hydrotalcite droplet on silica surface and the Marangoni effect was also investigated. The presence of PVA in hydrotalcite sols was found to influence the rheological properties of the sols significantly, resulting in higher viscosity and ultimately leading to lower contact angle on solid surfaces. The degree of hydrotalcite's philicity on a substrate was improved by the addition of PVA solution. In this study, the spreading of a liquid droplet on a solid surface controlled by a surface tension gradient, due to Marangoni effect was found to drive better spreading of the liquid droplet. Marangoni Number, Ma was found to be proportionally related with the surface tension of the sols but inversely proportional to contact angles of the sols. Marangoni forces that decreased the contact angle, promoted spreading of hydrotalcite droplets on the selected glass substrates.Keywords: contact angle, hydrotalcite, marangoni effect, spreading, wetting evolution